Recent Updates on the Involvement of PI3K/AKT/mTOR Molecular Cascade in the Pathogenesis of Hyperproliferative Skin Disorders - Mercurio, Laura; Albanesi, Cristina; Madonna, Stefania (Frontiers in Medicine, 2021)
PhosphoInositide-3 Kinase (PI3K) represents a family of different classes of kinases which control multiple biological processes in mammalian cells, such as cell growth, proliferation and survival. Class IA PI3Ks, the main regulators of proliferative signals, consists of a catalytic subunit (alpha, beta or delta) that binds p85 regulatory subunit and mediates activation of AKT and mammalian Target Of Rapamycin (mTOR) pathways and regulation of downstream effectors. Dysregulation of PI3K/AKT/mTOR pathway in skin contributes to several pathological conditions characterized by uncontrolled proliferation, including skin cancers, psoriasis and atopic dermatitis (AD). Among cutaneous cancers, basal cell carcinoma (BCC) and cutaneous squamous cell carcinoma (cSCC) display PI3K/AKT/mTOR signaling hyperactivation, implicated in hyperproliferation and tumorigenesis, as well as in resistance to apoptosis. Upregulation of mTOR signaling proteins has also been reported in psoriasis, in association with enhanced proliferation, defective keratinocyte differentiation, senescence-like growth arrest and resistance to apoptosis, accounting for major parts of the overall disease phenotypes. On the contrary, PI3K/AKT/mTOR role in AD is less characterized, even though recent evidence demonstrates the relevant function for mTOR pathway in the regulation of epidermal barrier formation and stratification. In this review, we provide the most recent updates on the role and function of PI3K/AKT/mTOR molecular axis in the pathogenesis of different hyperproliferative skin disorders, and highlights on the current status of preclinical and clinical studies on PI3K-targeted therapies.